Comparative Efficiency Analysis of Zakat Institutions in Indonesia: A Data Envelopment Analysis Approach - Nisak, Khoirun (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2025)
Introduction: Zakat is an important Islamic economic instrument and has an important economic impact for income distribution in society. Therefore, Zakat Institution should manage zakat in an appropriate and efficient way. This study aims to examine the efficiency of Zakat Institution based on its cluster which are government, national scale and local scale. Research Methods The research method employed is quantitative non-parametric analysis using Data Envelopment Analysis (DEA) to measure the efficiency of zakat management across different zakat institutions scales. The input variables used are amil salaries (X1), socialization costs (X2), operational costs (X3), and the number of offices (X4). The output variables are the amount of zakat collected (Y1) and the amount of zakat distributed (Y2). Results: The analysis results show that local-scale zakat institution, particularly LAZ Al-Kahfi Peduli, exhibit the highest efficiency, maintaining a perfect score for four consecutive years, although there was a slight decline in the last observed year. BAZNAS, representing government-owned, ranks second in efficiency, while national-scale zakat institutions rank third. Among the national-level zakat institutions, LAZISNU and Rumah Zakat stand out as the most efficient. Conclusion: Improvement recommendations are proposed for each zakat institutions based on benchmarks that can be used to optimize the input-output relationship in zakat management. The limitations of this study include incomplete financial reports published by zakat institutions. The government may consider stricter regulations requiring zakat institutions to conduct financial audits and publish financial reports on their websites to enhance accountability and public trust in these institutions.